Criminalisation of Indian Politics - Shah, Mohd Saqib (Innovative Research Thoughts, 2018)
The practise of criminalising political activity in India is a severe problem that has dogged the democratic system of the nation for many years. In this context, infiltration refers to the process through which criminals and persons with a track record of criminal activity enter the political arena, therefore creating a connection between politics and criminal activity. This has resulted in a flawed electoral process, in which politicians with criminal histories routinely win elections and hold public office. This has led to a compromised electoral process. The pervasiveness of corrupt practises, favouritism within the political system, and an absence of openness are the fundamental reasons why this issue exists. The necessity for cash during elections is a major factor that contributes to the close relationship that exists between politicians and criminals. Political parties often accept contributions from persons with questionable histories. It has far-reaching ramifications, including the deterioration of public faith in the political system and the undermining of democracy, which are both caused by the criminalization of politics. In addition to this, it has a direct effect on law and order since criminals in positions of power may use such positions to protect themselves from legal prosecution and commit crimes without fear of repercussions. In order to combat the criminalization of politics, a number of different measures have been proposed. These measures include the imposition of stricter criteria for candidates who are contesting elections, the expeditious disposal of criminal cases brought against politicians, and the disclosure of criminal records of candidates by political parties. However, as a result of political meddling and a general lack of political will, the implementation of these policies has been sluggish and often inefficient. In order to effectively solve the problem of the criminalization of politics in India, there must be a coordinated effort on the part of all of the relevant stakeholders, including political parties, civil society groups, and the judicial system. The only way for the nation to have any chance of reestablishing the purity of its democratic process and ensuring that those in power are responsible to the people whom they serve is if everyone works together.